Peningkatan Keterampilan Menulis Fiksi melalui Project Based Learning Berbantuan Pop Up Story Book di Sekolah Dasar - Agenina, Karnelia; Wahyuningsih, Arum; Utami, Sri (Journal Prakarsa Paedagogia, 2025)
This study aimed to improve the fictional story writing skills of third-grade elementary school students through the implementation of Project Based Learning (PjBL) assisted by a Pop Up Story Book. The research employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were 24 third-grade students of SDN Rejoagung 01, Trangkil District, Pati Regency. Data were collected through fictional story writing tests, classroom activity observations, and documentation. Data analysis was carried out using descriptive quantitative methods by calculating the percentages and mean scores achieved in each cycle, supported by qualitative analysis to interpret the dynamics of the learning process and changes in students’ learning behaviors. The results demonstrated a consistent improvement in students’ fictional writing skills, increasing from 59% in the pre-cycle to 71% in Cycle I and reaching 89% in Cycle II. Improvements were observed in several aspects, including content quality, completeness of story structure, accuracy of diction and sentence construction, correct use of spelling, and the utilization of references in story development. The implementation of PjBL encouraged students to plan, draft, revise, and present their written products systematically, while the Pop Up Story Book functioned as an idea stimulator and visual support that enriched plot development and character depiction. These findings confirm that Project Based Learning assisted by a Pop Up Story Book is effective in enhancing students’ creativity, collaboration, and learning responsibility in Indonesian language instruction at the elementary school level.